Team and Coach Gender: The Effect of the Expletive Halftime Speech - Carrington Ream; Hoyoon Jung; Bomin Paek (Journal of Coaching and Sports Science, 2024)
Although expletive use is considered taboo in most societies, expletives are commonly used in sports. However, the impact of expletives on coaching effectiveness has not received significant attention because of the unique nature of sports in which fierce competition is condoned and even encouraged.Inthe current study, the researchers aim to examine whether expletives alter the effectiveness of speeches given by coaches across genders. Collecting data from a total of 133 respondents, ANOVA demonstrated that expletive word use during halftime speeches by coaches did not play a role in diminishing the coaching effectiveness, regardless of the coach's gender and the players' gender. Additionally, male and female participants perceived expletive speech differently, and student-athletes rated the speeches as significantly more effective than the nonstudent-athletes. This study suggests practical implications for female coaches, who may consider stepping out of traditional expected roles (e.g., supportive and caring) and adopting language in coaching traditionally reserved for male coaches, given that their choice of language will not negatively impact their coaching effectiveness. However, further examination is needed for the robustness of our findings as the current study does not necessarily demonstrate an increase in effectiveness or a positive shift in perceptions from the use of expletives.